Cross-Linguistic Orthographic Effects in Late Spanish/English Bilinguals - Christopher A. Dean; Jorge R. Valdés Kroff (Languages, 2017)
Through the use of the visual world paradigm and eye tracking, we investigate how orthographic–phonological mappings in bilinguals promote interference during spoken language comprehension. Eighteen English-dominant bilinguals and 13 Spanish-dominant bilinguals viewed 4-picture visual displays while listening to Spanish-only auditory sentences (e.g., El detective busca su banco ‘The detective is looking for his bench’) in order to select a target image. Stimuli included two types of trials that represent potential conflict in bilinguals: b-v trials, e.g., banco-vaso ‘bench-glass’, representing homophonous phonemes with distinct graphemic representations in Spanish, and j-h trials, e.g., juego-huevo ‘game-egg’, representing interlingual homophonous phonemes with distinct graphemic representations. Data were collected on accuracy, reaction time (RT), and mean proportion of target fixation. Reaction Time results indicate that Spanish-dominant speakers were slower when the competitor was present in b-v trials, though no effects were observed for English-dominant speakers. Eye-tracking results indicate a lack of competition effects in either set of trials for English-dominant speakers, but lower proportional target fixations for Spanish-dominant speakers in both sets of trials when an orthographic/phonological distractor was present. These results suggest that Spanish-dominant bilinguals may be influenced by the orthographic mappings of their less-dominant L2 English, providing new insight into the nature of the interaction between the orthography and phonology in bilingual speakers.